Daguerreotypes at Harvard - Harvard University - Library (2009)
[Dt.:] Daguerreotypiensammlung der Harvard University Library, durchsuchbar nach Titel, Name, Inhalt und Genre in den Kategorien Daguerreotypists and Studios, Harvard Repositories und Portrait Sitters. - [Engl.:] Collection of daguerreotypes at Harvard University Library; you can search for titles, names, subjects and genres in the categories Daguerreotypists and Studios, Harvard Repositories und Portrait Sitters.